The Maternal Sociodemographic Determinants of Low Birth Weight in Indonesia - Yulinda Nurul Aini; Fuat Edi Kurniawan (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
LBW is one of the highest predictors of infant and child mortality. In Indonesia, more than 100 thousand newborns experience LBW cases. In addition to birth intervals, there are maternal sociodemographic factors that can explain cases of LBW, such as age, parity, location of residence, marital status, education, and level of maternal welfare. For this reason, this study aims to analyze the association between birth intervals and maternal sociodemographic factors in LBW cases using the 2017 IDHS data. The study results show that 1 in 10 babies is born with LBW. More than half are found in rural areas, with secondary education of the mother, and in the poorest conditions. SRS results show that birth interval has no significant association with LBW. However, from the results of MLR, birth interval, parity, mother's age, residency, education, and the interaction between education and birth interval are significant determinants of LBW. Mothers who have children with short (24 months) or long (48 months) birth intervals, live in urban areas, have a lower level of education, and are under 20 or over 35 years old have a greater chance of giving birth to LBW babies. Meanwhile, mothers with more children have a slight chance of giving birth to LBW babies. These findings show the critical role of family planners in educating partners and parents in Indonesia regarding the potential risks of LBW babies according to the mother's sociodemographic condition.